Pengembangan Sistem Informasi Manajemen Surat Masuk dan Keluar (Studi Kasus: Puskesmas Kecamatan Cipayung) - Junjungan Siregar; Satrio Agung Wicaksono; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Cipayung District Health Center is one of 84 health centers in East Jakarta. There are several problems on the service of the Cipayung District Health Center including the requests for outgoing letters that are not in one door, incoming mail storage, and time-consuming preparation of a letter agenda report. The method used in this development is the waterfall. System design is done by using UML diagrams such as sequence diagrams, class diagrams, and use case diagrams. At the implementation stage, the system uses the CodeIgniter 4 framework to facilitate development by applying an object-oriented approach. In addition, the system uses the myth-auth library for the authentication process and MySQL for the DBMS. At the testing stage, validation tests are carried out to determine whether the system made is appropriate and user acceptance tests are carried out to measure user acceptance. The results of the validation test resulted in a value of 100% from 16 test cases and an average of 100% for the user acceptance test which was carried out on 2 people.